Dendritic cells in multiple myeloma: from immune evasion to therapeutic potential - Jordan, Melanie Andrea; Morschl, Johannes; Autenrieth, Stella E. (Frontiers in Immunology, 2025)
Multiple myeloma (MM) is a type of hematologic cancer characterized by the uncontrolled clonal expansion of plasma cells in the bone marrow (BM). This leads to significant dysfunction and suppression of the immune system in affected patients. Myeloma cells employ sophisticated strategies to manipulate immune and non-immune cells, evading immune surveillance and enhancing their survival. One key factor in this evasion is the disruption of dendritic cell (DC)-mediated immune mechanisms. Extensive evidence indicates that in the presence of myeloma cells, DC numbers are notably reduced, and their phenotype and function are altered, impairing their ability to present antigens and activate robust T-cell responses effectively. Despite rapid advances in MM treatment, with promising strategies such as DC-based vaccines being already achieved, DC dysfunction remains a substantial hurdle, associated with or contributing to poor therapeutic outcomes, disease relapse, and MM’s persistence as an incurable disease. To address these challenges, it is essential to understand the intricate mechanisms through which myeloma cells transform DCs into their “accomplices,” undermining immune responses. This review comprehensively summarizes the current understanding of the role of DCs in MM. Additionally, it evaluates the potential of DCs in anti-MM immunotherapy, discussing persistent challenges and highlighting emerging perspectives that may lead to promising breakthroughs for improved patient outcomes.